f(x) = e^2x (x^3 + 1)
It can also be written as it follows:
![f(x)=e^(2x)\cdot(x^3+1)](https://img.qammunity.org/2023/formulas/mathematics/college/y972rp8djm78q0xaaz37e60q9wkwzko80l.png)
first we need to determine f'(x).
we can see this function as a product of two funcions:
![\begin{gathered} f(x)=g(x)\cdot h(x) \\ g(x)=e^(2x);h(x)=x^3+1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ynouwlpi3ulygxqctzvp0byza7iz04xgkm.png)
so, we can apply the Product rule
![(d)/(dx)\lbrack g(x)\cdot h(x)\rbrack=g(x)\cdot h^(\prime)(x)+g^(\prime)(x)\cdot h(x)](https://img.qammunity.org/2023/formulas/mathematics/college/vp9j2drtjgfrxf3mr9iunlw5qnid453d19.png)
Let's determine the derivate of those two function
![\begin{gathered} g(x)=e^(2x) \\ g^(\prime)(x)=2\cdot e^(2x) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kcegzowfa9gw384dihdz2t2joa9wd7u9yn.png)
![\begin{gathered} h(x)=x^3+1 \\ h^(\prime)(x)=3x^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jhsepplt98voxg7y6uliiu35925602ur6n.png)
Now, we can use the functions g(x) and h(x) and its derivates to determine f'(x) using the Product rule
![\begin{gathered} f^(\prime)(x)=g(x)\cdot h^(\prime)(x)+g^(\prime)(x)\cdot h(x) \\ f^(\prime)(x)=e^(2x)\cdot3x^2+2e^(2x)\cdot(x^3+1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/f7jbx6jw8shg2jrdpytyy0csp8cu8gskfn.png)
we can simplify this expression as it follows:
![\begin{gathered} f^(\prime)(x)=3e^(2x)x^2+2e^(2x)x^3+2e^(2x) \\ f^(\prime)(x)=2e^{\mleft\{2x\mright\}}x^3+3e^{\mleft\{2x\mright\}}x^2+2e^{\mleft\{2x\mright\}} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pgrv5dn6663515u4cgp799c69fj8uclo5m.png)
Finally, we need to replace x = 2 to find f'(2)
![f^(\prime)(2)=2e^{\{2\cdot2\}}\cdot2^3+3e^{\{2\cdot2\}}\cdot2^2+2e^{\{2\cdot2\}}](https://img.qammunity.org/2023/formulas/mathematics/college/qr41h8exr7j8n934ldxkyjbcxypi2jbfgl.png)
simplify:
![\begin{gathered} f^(\prime)(2)=2e^4\cdot8+3e^4\cdot4+2e^4 \\ f^(\prime)(2)=16e^4+12e^4+2e^4^{} \\ f^(\prime)(2)=(16+12+2)\cdot e^4 \\ f^(\prime)(2)=30e^4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/x7t8yx8ot433kx1hws9s2tuak33rhqgai6.png)